Potret Buram Perlindungan Tenaga Kerja Indonesia (TKI) - S. Djuni Prihatin (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2007)
Despite the advantages of sending manual labours overseas, Indonesia fails to set up a relinble scheme to protect them from abuse. Improvement of the quality of the labours, tightening control over the brokery agencies as well as legal and administrative reform are required to do so.